Decompensation of chronic heart failure after COVID-19: a clinical observation - Marina V. Moiseeva; Natalya V. Bagisheva; Anna V. Mordyk; Dmitry I. Trukhan; Victoria V. Streltsova; Irina I. Dubrovskaya (LLC "MEDIAFORMAT", 2023)
Chronic heart failure is a clinical syndrome that develops as a result of various diseases of both the cardiovascular and other systems, aggravates the course of the underlying disease, and increases the risk of an unfavorable outcome. The development of coronavirus infection in patients with CHF implies both the likelihood of symptom manifestation and the development of decompensation of the condition as a result of their mutual aggravation, which requires additional efforts from the doctor in their treatment to prevent disability and mortality. A case of dynamic follow-up of a patient with chronic heart failure that developed as a result of myocarditis is presented. After a COVID-19 infection, a progressive increase in clinical symptoms, loss of control, and decompensation of the condition were observed for six months, which required correction of drug and non-drug therapy to improve the prognosis for life.